2014
DOI: 10.1186/1471-2334-14-509
|View full text |Cite
|
Sign up to set email alerts
|

Associations of hand-washing frequency with incidence of acute respiratory tract infection and influenza-like illness in adults: a population-based study in Sweden

Abstract: BackgroundFrequent hand-washing is standard advice for avoidance of respiratory tract infections, but the evidence for a preventive effect in a general community setting is sparse. We therefore set out to quantify, in a population-based adult general population cohort, the possible protection against acute respiratory tract infections (ARIs) conferred by a person’s self-perceived hand-washing frequency.MethodsDuring the pandemic influenza season from September 2009 through May 2010, a cohort of 4365 adult resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…This might be due to the fact that self-reported handwashing practice is from a simple cleansing to the appropriate level of recommended duration and method of handwashing. However, the lack of association in the current study is in line with a population-based study in Sweden [59]. In the current study children of mothers who have reported a lack of information about handwashing were more likely to be at higher risk of ARI.…”
Section: Discussionsupporting
confidence: 82%
“…This might be due to the fact that self-reported handwashing practice is from a simple cleansing to the appropriate level of recommended duration and method of handwashing. However, the lack of association in the current study is in line with a population-based study in Sweden [59]. In the current study children of mothers who have reported a lack of information about handwashing were more likely to be at higher risk of ARI.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, we assume that in an airport population of N individuals, only the 70%·67%=49.6% of N are compliers with effective hand washing. Furthermore, we assume that each individual washes his/her hands on average between 4 and 10 times per day (Merk, Kühlmann‐Berenzon, Linde, & Nyrén, ), which means that in a 24‐hour time frame, one event of hand washing takes place every 2.5–6 hours. We assume that the frequency of hand washing follows a normal distribution with mean equal to 4.5 hours and standard deviation equal to 1 hour.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we assume that in an airport population of N individuals only the 70% · 67% = 49.6% of N are compliers with effective hand washing. Furthermore, we assume that each individual wash their hands on average between 4-10 times per day 41 which means that in a 24-hour timeframe one event of hand washing takes place every 2.5-6 hours. We assume that the frequency of hand washing follows a normal distribution with mean equal to 4.5 hours and standard deviation equal to 1 hour.…”
Section: Status Quo Of Hand Washing Engagement Ratementioning
confidence: 99%